Research Ethics Committees and subjects Vulnerability: an experience report - Valdecir Batistiolle, João; da Silva Júnior, Walter José (O Mundo da Saúde, 2006)
his article aims to present the results of a research carried through with some Research Ethics Committees of São Paulo State in order to verify whether these committees are accomplishing their assigned purpose, that is, to guarantee the protection of the rights and the dignity of the human beings involved in scientific experimentations. More specifically, it has the intention to reflect on those aspects related to the vulnerability of research subjects. This report of experiences aims to reflect on people involved in the activities of the Committees in particular the responsible secretaries, and to study available archived documents. The Research Ethics Committees chosen had been from the Pontifical Catholic University of São Paulo (PUC-SP), PUC-Sorocaba, São Camilo University Center, Dante Pazzanese Hospital, Hospital of the Clinics of the Medical School of University of São Paulo (USP), Federal University of São Paulo (UNIFESP) and College of Public Health of USP. In accordance with data gathered, there is a concern with the protection of research subjects, to prevent abuses and disrespect to their dignity. It was also observed that the main reason of research projects non-approval has been the inadequate or insufficient filling of the Free and Informed Consent Statement (FICS). Anyway, the committees are still in a process of evolution and improvement. Nevertheless, it remains as desirable to extend internal pluralism and the bonds between the committees. Only then will bioethical reflection have justified the reason of its existence as a language for mediating conflicts and interests in research and experimentation with human beings.